Káromkodásból katedrálist: lelkigondozás és spiritualitás összefüggései "Jób könyvé"ben - Ágnes BÁLINT (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
A Cathedral Built on Swearing? Interrelations between Counselling and Spirituality in the Book of Job. Given its enormous exegetical potential, pastoral care could clearly lay hold more of the Book of Job’s kerygmatic rather than its psychological certainties. In addition to the Book of Job being often read as a case study about the suffering person’s sense of justice and quest for meaning, Job’s experience has a spiritual overtone as well: he is faced with the question of the true nature of God and the need to find an adequate human response to it. Also, the Book is indicative of how people respond to the suffering and what witness and support they offer. In this paper, I evaluate the counselling strategies in the Book of Job identified by Manfred Oeming. I pay special attention to Job’s wife, and I argue that she should not be considered a proper counsellor, as she herself is stricken by the same tragic events as is Job. Instead, she is a fellow sufferer, although acknowl-edged as such only by extracanonical literature. What is more, she may be iden-tified as the partner or the first and foremost caregiver of the sufferer whose chal-lenges and difficulties remain unidentified, unspoken of, and unaddressed most of the time. As for the spiritual issues aroused by suffering, I suggest that both counsellor and counsellee must reach spiritual maturity to be able to understand and accept their experience of suffering as a genuine experience of God, and so, given time, this may make space for God’s theophany and healing presence.